2014
DOI: 10.1093/molehr/gau112
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent triploidy due to a failure to complete maternal meiosis II: whole-exome sequencing reveals candidate variants

Abstract: Triploidy is a relatively common cause of miscarriage; however, recurrent triploidy has rarely been reported. A healthy 34-year-old woman was ascertained because of 18 consecutive miscarriages with triploidy found in all 5 karyotyped losses. Molecular results in a sixth loss were also consistent with triploidy. Genotyping of markers near the centromere on multiple chromosomes suggested that all six triploid conceptuses occurred as a result of failure to complete meiosis II (MII). The proband's mother had also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 56 publications
0
28
0
3
Order By: Relevance
“…In that particular study, the majority of diandric triploids had developmental ages in excess of 8.5 weeks, whereas most of the digynic triploids have aborted earlier, before developmental age 8.5 weeks, and this difference in distribution was highly significant. Other authors also found a predominance of paternal triploidy over maternal, but the cases examined were in the [11][12][13][14] th week of pregnancy [14]. On the other hand, McFadden et al (2006) reported higher incidence of digynic triploidy, but their series, the same as ours, evaluated early spontaneous abortions [15].…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In that particular study, the majority of diandric triploids had developmental ages in excess of 8.5 weeks, whereas most of the digynic triploids have aborted earlier, before developmental age 8.5 weeks, and this difference in distribution was highly significant. Other authors also found a predominance of paternal triploidy over maternal, but the cases examined were in the [11][12][13][14] th week of pregnancy [14]. On the other hand, McFadden et al (2006) reported higher incidence of digynic triploidy, but their series, the same as ours, evaluated early spontaneous abortions [15].…”
Section: Discussionmentioning
confidence: 49%
“…Digynic triploidy may be the result of fertilisation of a diploid ovum by a single sperm, with the diploid ovum being the result of an error in either the first (MI) or second (MII) meiotic division [11]. Whatever the origin of the extra chro- , who analysed 14 cases of triploidy, virtually all triploids are a consequence of an error in the ovum: either a division error leading to digyny or an abnormality of the ovum that fails to block fertilisation by more than one sperm [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal NLPR7 mutations were also involved in a few cases of diandric triploidies including 1 case of recurrent triploidy [Slim et al, 2011]. Recurrent digynic triploidy is more infrequent; to our knowledge, it has been reported in 5 cases [Pergament et al, 2000;BarAmi et al 2003;Brancati et al, 2003;Huang et al, 2004;Filges et al, 2015], although not in all triploid pregnancies a molecular investigation was performed. We are not aware of other cases with combination of a digynic triploidy and a zygotic tetraploidy with a PPMM contribution.…”
Section: Resultsmentioning
confidence: 77%
“…Unlike most chromosomal abnormalities, increased maternal age is not a risk factor for digynic or diandric triploidy. However, there have been several reports of recurrent (≥3 times) triploidy [16][17][18], and one study examined possible genetic vari-ants responsible for this phenotype [19]. These reports support the need for chromosome diagnosis in early pregnancy loss.…”
Section: Discussionmentioning
confidence: 93%